Effect of bacterial growth period on the sensitivity of the MTT assay for silver - Halmi M.I.E.; Ahmad F.; Hashim A.K.; Shamaan N.A.; Syed M.A.; Shukor M.Y. (Triveni Enterprises, 2024)
Indexed by WOS/ Scopus